Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick (Tongkat Berjalan) Dalam Meningkatkan Hasil Belajar Pada Kompetensi Dasar Menganalisis Keterampilan Gerak Permainan Bola Besar - Fitra Syam, M. (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
This research aims to improve student learning outcomes by using the Talking Stick learning model assisted by image media in the PJOK subject for class XI Economics at SMA Negeri 8 North Penajam Paser for the 2020/2021 academic year. This type of research is classroom action research. The research results show an increase in student learning outcomes after using the Talking Stick learning model. Based on research results, the average score of learning outcomes for class Seeing that the scores obtained by students from cycle I to cycle II have increased, it can be stated that the application of the Talking Stick model can improve the learning outcomes of XI Economics students at SMA Negeri 8 Penajam Paser Utara and students' responses to learning activities through cooperative learning type Talking Stick class Economics at SMA Negeri 8 Penajam Paser Utara, most students responded positively.